Measurement of sexual health outcomes among people who inject drugs: pilot study in Catalonia, Spain and Barnaul, Russia - Cinta Folch; Lev Zohrabyan; Natalia Vagaitseva; Jordi Casabona; Igor Toskin; the local REDAN Group (BMC, 2018)
Abstract Background The main objective of this study was to test some of the draft sexual health indicators developed by the World Health Organization as part of a comprehensive indicator framework to monitor progress in universal access to reproductive health. Methods Cross-sectional studies among people who inject drugs were conducted in Catalonia (n = 734) and Barnaul (n = 500). 'Sexual competency' was measured using three indicators: sexual satisfaction, sexual safety, and sexual autonomy. Individual social norms on sexuality were also collected. The construct validity of the sexual safety and sexual autonomy items were assessed. Multivariate logistic regression models explored factors associated with sexual dissatisfaction. Results In Catalonia, sexual competency was higher among males than females who inject drugs (60.4% versus 33.3%). In both Catalonia and Barnaul, differences by sex in social norms on sexuality were seen. Mean scores on sexual safety (4.15 in Catalonia and 3.54 in Barnaul) were lower among participants who reported not using condoms. Mean scores on sexual autonomy (4.42 in Catalonia and 3.97 in Barnaul) were lower among those who had experienced some form of sexual assault. Perceived sexual safety, sexual autonomy, and social norms on sexuality were associated with sexual dissatisfaction. Conclusions The sexual health indicators tested are valid, feasible, and reliable tools to monitor and evaluate sexual health programs and activities. The results confirm that sexual satisfaction depends on safe sexual experiences, free from coercion and violence. Social norms and individual perceptions about sexual health need to be considered when developing national disease prevention programs.